2020
DOI: 10.1002/elps.202000201
|View full text |Cite
|
Sign up to set email alerts
|

Development of a microwave‐assisted extraction method for the recovery of bioactive inositols from lettuce (Lactuca sativa) byproducts

Abstract: A microwave-assisted extraction (MAE) method was developed for the extraction of bioactive inositols (D-chiro-and myo-inositols) from lettuce (Lactuca sativa) leaves as a strategy for the revalorization of these agrofood residues. Gas chromatography-mass spectrometry was selected for the simultaneous determination of inositols and sugars (glucose, fructose, and sucrose) in these samples. A Box-Behnken experimental design was used to maximize the extraction of inositols based on the results of single factor tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Extractions under these conditions led to a significant increase in inositol concentration of up to 70%, i.e., 1126 mg/L (Figure 4). Zuluaga et al [14] obtained inositol from different lettuce types using a microwave-assisted extraction process. The highest inositol concentration (5.42 mg/g dry sample) was obtained using a liquid-solid ratio of 100:1, performing one extraction for 30 min at 40 • C, with an ethanol-water mixture as the solvent.…”
Section: Inositolmentioning
confidence: 99%
See 1 more Smart Citation
“…Extractions under these conditions led to a significant increase in inositol concentration of up to 70%, i.e., 1126 mg/L (Figure 4). Zuluaga et al [14] obtained inositol from different lettuce types using a microwave-assisted extraction process. The highest inositol concentration (5.42 mg/g dry sample) was obtained using a liquid-solid ratio of 100:1, performing one extraction for 30 min at 40 • C, with an ethanol-water mixture as the solvent.…”
Section: Inositolmentioning
confidence: 99%
“…For instance, inositol supplements are frequently used to treat anxiety and stress while also exhibiting beneficial effects in other disorders. Despite some authors having reported the extraction of inositol from natural sources, such as mung beans and lettuce [13,14], its potential extraction from olive cake has not been previously studied by other authors. The extraction process was optimized by identifying the most suitable solvent and exploring the influence of the operating variables (i.e., temperature, time, solvent/extract ratio, number of extraction stages, and pH) on the extraction yield.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction of bioactive carbohydrates from fruits, vegetables, and legumes have been usually carried out by conventional solid-liquid extraction (SLE) [13][14][15][16]. However, there is a growing interest in applying more efficient advanced extraction techniques which help to break vegetable tissues, releasing bioactive compounds from cell structures, as an alternative to the tedious and time-consuming SLE-based processes [17,18]. Among the most outstanding implemented techniques, Microwave Assisted Extraction (MAE) is preferred for its speed, efficiency, and safe operation [16,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a growing interest in applying more efficient advanced extraction techniques which help to break vegetable tissues, releasing bioactive compounds from cell structures, as an alternative to the tedious and time-consuming SLE-based processes [17,18]. Among the most outstanding implemented techniques, Microwave Assisted Extraction (MAE) is preferred for its speed, efficiency, and safe operation [16,[18][19][20][21]. During conventional treatments, heat energy is delivered through conduction-convection processes with the consequent loss of heat energy to the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation